Educational Innovation in the Utilization of the MCH Handbook as an Early Intervention for Toddler Growth and Development in Pong Murung Village, Manggarai Regency - Damat, Afrinita; Dewi, Imelda R.; Bandur, Paskalinda M. Y.; Hamat, Viviana; Centis, Maria C. L. (PROMOTOR, 2025)
The low utilization of the Maternal and Child Health (MCH) Handbook in Pong Murung Village hinders the early detection of toddler growth and development issues. This community service program aimed to enhance mothers' knowledge through educational sessions and practical demonstrations on the use of the MCH Handbook as an early intervention tool. The activities included lectures, discussions, and hands-on demonstrations conducted for 15 mothers of toddlers on March 12, 2025. Evaluation was carried out using pre- and post-tests. Results showed an increase in knowledge from poor (80%) to good (60%). The findings demonstrated that direct mentoring effectively improves mothers’ understanding of how to independently use the MCH Handbook to monitor child development. A major obstacle was that many handbooks were kept at health posts, limiting access for mothers. A sustainable solution includes returning the handbook to parents and providing continued education by village midwives. This activity highlights the importance of cross-sector collaboration to optimize the MCH Handbook as a tool for education and early detection of child development issues.